An in situ and general preparation strategy for hybrid metal/semiconductor nanostructures with enhanced solar energy utilization efficiency1. Issue 28 (28th July 2015) - Bai, Hua; Ye, Fang; Lv, Qing; Xi, Guangcheng; Li, Junfang; Yang, Haifeng; Wan, Chongqing
<x xml:space="preserve">Abstract</x> We report a facile method for direct growth of noble metal nanoparticles on semiconductor nanostructures through an in situ redox reaction.